CaCO3 / PVC nano composite material and preparation method thereof
Through the binding and suspension polymerization reaction of modified nanoCaCO3 and vinyl chloride monomers and the problems of low elongation of break and insufficient dispersion of CaCO3/PVC nanocomposites were solved, and the high mechanical properties and transparency were improved, which simplified the Process flow and reduce production costs.
Patent Information
- Application Number
- CN202310849197.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-17
AI Technical Summary
The existing CaCO3/PVC nanocomposites have low elongation of breakage and insufficient compatibility and dispersion of nanoCaCO3 with PVC matrix, resulting in limited improvement in the mechanical properties of the materials, and the complex traditional preparation process is not conducive to industrial production.
Modified nano CaCO3 and vinyl chloride monomer stir at room temperature to form a transparent or translucent vinyl chloride phase dispersion, combined with suspended polymerization aid and water to form a monodispersed nano CaCO3/PVC composite resin, and pass Post-processing was made to prepare CaCO3/PVC nanocomposites with high elongation of break and impact strength.
The nano CaCO3 monodispersion in PVC was achieved, which significantly improved the elongation of break, impact strength and transparency of composite materials, simplified the process flow, reduced production costs, and expanded the application field of materials in hard transparent plastic products. .
Smart Images

Figure CN119320535A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic nanoparticle / polymer nanocomposite materials and preparation thereof, and in particular to a CaCO3 / PVC nanocomposite material and a preparation method thereof. Background Art
[0002] CaCO3 is a common mineral carbonate, which exists in the form of natural mineral salt in nature, and the raw materials are cheap and easy to obtain. Combining the advantages of nanomaterials themselves, quantum size effect, small size effect, surface effect and macro quantum effect, nano CaCO3 shows better performance than ordinary CaCO3. As an inorganic nano filler, nano CaCO3 has the effect of toughening and strengthening. While improving the mechanical properties of materials, it can also reduce the cost of raw materials. Therefore, nano CaCO3 has a wide range of applications in plastics, rubber, coatings and other fields.
[0003] PVC is a commonly used and inexpensive polymer material, which is widely used in products such as pipes, electrical insulators and building materials. However, pure PVC resin has the characteristics of poor toughness and thermal instability, which has many limitations in application. Therefore, in specific industrial applications, PVC is modified and post-processed to prepare related materials to improve its mechanical properties and thermal stability, such as modification by blending with rubber materials, organic and inorganic nanomaterials, and then post-processed to prepare PVC materials.
[0004] For CaCO3 / PVC binary nanocomposites, the compatibility between CaCO3 filler and PVC matrix and its dispersion uniformity in the nanocomposite resin and the final composite material play a crucial role in the performance of the composite material. The traditional way to prepare CaCO3 / PVC nanocomposite materials is to simply mechanically blend nano-CaCO3 and PVC resin and extrude them into granules. Due to the large difference between the hydrophilic and oleophobic properties of nano-CaCO3 and the surface properties of the polymer, phase interface and uneven dispersion or even agglomeration of nano-CaCO3 in the composite material are prone to occur, which damages the mechanical properties of the PVC material itself. Therefore, those skilled in the art improve the problems of uneven dispersion and agglomeration by modifying nano-CaCO3. Since the modified nano-CaCO3 improves its interfacial compatibility with PVC, the phase separation phenomenon of the composite material is improved, and its dispersion problem in the composite material is also partially solved. For example, the Chinese patent publication No. 100368444C, entitled "Preparation method of vinyl chloride / nano-CaCO3 in-situ polymerization composite resin", discloses the following technical scheme: first prepare a seed emulsion of PVC, use the seed emulsion of PVC to perform surface treatment on nano-CaCO3 to obtain an emulsion of nano-CaCO3 filler, then pre-mix it with vinyl chloride, and then perform in-situ polymerization. The composite resin is synthesized by reaction, and a composite material with high impact strength is prepared through post-processing. During this process, some nanoparticles disintegrate due to the heat accumulation of the internal polymerization reaction and the stress change caused by the filling polymerization of the monomer in the nano-channel, so the nano-CaCO3 is not monodispersed in PVC, and the dispersion problem has not been completely solved. Therefore, the improvement of the overall mechanical properties of the polymer is limited, and the preparation process of the invention is complicated, which is not conducive to industrial production. The present invention directly uses the transparent or translucent monodisperse formed by the modified nano-CaCO3 solid in the monomer vinyl chloride of polyvinyl chloride as a raw material to carry out in-situ polymerization reaction to synthesize nano-composite resin, and then through post-processing to prepare CaCO3 / PVC nano-composite material. Nano-CaCO3 is uniformly dispersed in the vinyl chloride monomer with a particle size of 5-40nm without agglomeration, and the dispersibility of nano-CaCO3 is maintained during the in-situ polymerization process, so that nano-CaCO3 is monodispersed in the nano-composite resin and the nano-composite material obtained by post-processing of the resin, thereby improving the overall mechanical properties of the composite material. Summary of the invention
[0005] The first technical problem to be solved by the present invention is to provide a CaCO3 / PVC nanocomposite material, which can solve the problem of low elongation at break of general CaCO3 / PVC composite materials.
[0006] The second technical problem to be solved by the present invention is to provide a method for preparing a CaCO3 / PVC nanocomposite material. The preparation method can fundamentally solve the compatibility problem of nano-CaCO3 with a PVC matrix and the dispersibility problem in a PVC resin, and then after post-processing, a CaCO3 / PVC binary nanocomposite material with high elongation at break and impact strength and a derived CaCO3 / elastomer / PVC ternary nanocomposite material are prepared, and the post-processing process does not change the compatibility of the nano-CaCO3 with the PVC matrix and the dispersibility in the final composite material.
[0007] In order to solve the above-mentioned first technical problem, the present invention adopts the following technical solution:
[0008] A CaCO3 / PVC nanocomposite material, comprising the following materials:
[0009] CaCO3 / PVC nanocomposite resin 100 - 120 parts,
[0010] Heat stabilizer 1 - 6 parts,
[0011] Lubricant 0.5 - 2 parts;
[0012] The CaCO3 / PVC nanocomposite resin is synthesized from the following raw materials in parts by weight: a transparent or translucent vinyl chloride phase dispersion of nano-CaCO3, 4-6 parts of a suspension polymerization dispersant, and 0.1-0.3 parts of an initiator;
[0013] The transparent or translucent vinyl chloride phase dispersion of nano-CaCO3 comprises 100 parts of vinyl chloride and 8-20 parts of nano-CaCO3.
[0014] The nanocomposite material of the present invention has an elongation at break of 40%-60% and a notched impact strength of 4KJ / m 2 -8KJ / m 2 , the tensile yield strength is 55MPa-75MPa. Compared with the PVC material without adding nano-CaCO3, the tensile elongation at break is increased by more than 350%, the notch impact strength is increased by more than 200%, and the tensile yield strength is increased by more than 10%; nano-CaCO3 is monodispersed in the binary composite material with a particle size of 5-40nm.
[0015] As an embodiment, the heat stabilizer is a stabilizer commonly used in industrial production, selected from one of an organic tin stabilizer and a calcium zinc stabilizer.
[0016] The lubricant is selected from one of stearic acid lubricant and oxidized polyethylene lubricant.
[0017] As an embodiment, the CaCO3 / PVC nanocomposite material further comprises 5-20 parts of an elastomer, thereby forming a CaCO3 / elastomer / PVC ternary nanocomposite material.
[0018] The elongation at break of the ternary nanocomposite material of the present invention is 100%-260%, and the notched impact strength is 40KJ / m 2 -100KJ / m 2 , the tensile yield strength is 40MPa-60MPa. Compared with ordinary PVC, the elongation at break is increased by more than 400%, the notched impact strength is increased by more than 1000%, and the tensile yield strength is increased by more than 5%; compared with elastomer / PVC composite materials, the elongation at break is increased by more than 300%, the notched impact strength is increased by more than 400%, and the tensile yield strength is increased by more than 15%.
[0019] To solve the above second technical problem, the present invention adopts the following technical solution:
[0020] A method for preparing a CaCO3 / PVC nanocomposite material comprises the following steps:
[0021] 1) Adding nano-CaCO3 and vinyl chloride monomer into a polymerization kettle, stirring is started, and stirring is performed at room temperature for a period of time to form a transparent or translucent nano-CaCO3 vinyl chloride phase dispersion, which can be used as a raw material for synthesizing a nano-composite resin, and the dispersion can exist stably;
[0022] 2) After adding the suspension polymerization aid and water into the polymerization kettle, stirring and heating to the polymerization temperature to start the polymerization reaction;
[0023] 3) After a period of reaction, water is injected midway, and the reaction is continued. When the pressure of the kettle drops below 0.1 MPa, a terminator is added to terminate the reaction, stirring is stopped, and the material is discharged to obtain a suspension of nano-CaCO3 / PVC composite resin;
[0024] 4) The suspension is dehydrated and dried to obtain CaCO3 / PVC nanocomposite resin powder;
[0025] 5) Mechanically blending the CaCO3 / PVC nanocomposite resin powder, a heat stabilizer and a lubricant, and then injection molding or extrusion molding to obtain a CaCO3 / PVC binary nanocomposite material; or mechanically blending the CaCO3 / PVC nanocomposite resin powder, a heat stabilizer, a lubricant and an elastomer, and then injection molding or extrusion molding to obtain a CaCO3 / elastomer / PVC ternary nanocomposite material.
[0026] As an embodiment, in step 1), the added amounts of nano-CaCO3 and vinyl chloride monomer are 8-20 parts and 100 parts respectively, and the stirring speed and stirring time are 500r / min-1500r / min and 15min-30min respectively.
[0027] As an embodiment, the suspension polymerization aid in step 2) is composed of 4-6 parts of suspension polymerization dispersant, 0.1-0.3 parts of initiator, 0.05-0.15 parts of pH regulator, the amount of water added is 50-150 parts, the stirring time is 20min-30min, and the polymerization temperature is 50℃-65℃.
[0028] Wherein, the suspension polymerization dispersant is a mixture of a cellulose dispersant and polyvinyl alcohol, and the weight ratio of the cellulose dispersant to the polyvinyl alcohol is 3:7-7:3; preferably, the cellulose dispersant is selected from one of hydroxypropyl methylcellulose and methylcellulose;
[0029] The initiator is selected from a mixture of two or more of ammonium persulfate, potassium persulfate, and an organic peroxide; preferably, the organic peroxide is one of tert-butyl peroxydecanoate, isophenyl peroxydecanoate, tert-butyl peroxypivalate, tert-butyl peroxyoctanoate, and bis-(2-ethylhexyl) peroxydicarbonate;
[0030] The pH regulator is selected from one of ammonium bicarbonate, ammonia water and sodium bicarbonate.
[0031] As an embodiment, in step 3), the reaction period refers to 20-40 minutes of reaction, the amount of water added for the mid-injection is 150-250 parts, and the reaction time is 3-4 hours.
[0032] As an embodiment, in step 5), the amount of the heat stabilizer added is 1-6 parts, the amount of the lubricant added is 0.5-2 parts, and the amount of the elastomer added is 5-20 parts;
[0033] As a preferred embodiment, the heat stabilizer is a stabilizer commonly used in industrial production, preferably one selected from an organic tin stabilizer and a calcium zinc stabilizer;
[0034] The lubricant is selected from one of stearic acid lubricant and oxidized polyethylene lubricant.
[0035] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0036] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] Compared with the existing CaCO3 / PVC nanocomposite material, in the present invention, nano-CaCO3 has good compatibility with PVC, and the nano-CaCO3 and PVC resin are in a monodisperse state in the nanocomposite material prepared by post-processing; the elongation at break and impact strength of the CaCO3 / PVC binary nanocomposite material and the CaCO3 / elastomer / PVC ternary nanocomposite material are greatly improved compared with ordinary PVC materials, and the strength of the composite material is also improved while toughening, and the overall mechanical properties of the composite material are excellent, and the post-processing process does not change the compatibility of the nano-CaCO3 with the PVC matrix and the dispersibility in the final composite material. The synthesis process of the nano-composite resin is simple, and the preparation process of the composite material is the same as the industrial production method, but the application performance of the material is improved, the addition amount of the impact-resistant auxiliary agent in the preparation process is reduced, the production cost is reduced, and the binary nanocomposite material has good transparency without adding other auxiliary agents, and the application field of the CaCO3 / PVC binary nanocomposite material with high mechanical properties and transparency can be expanded to hard transparent plastic products, such as plastic glass and transparent plates, with better economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0040] Figure 1 This is a TEM image of the vinyl chloride dispersion of nano-CaCO3 in the raw material used to synthesize the nano-composite resin of the present invention. It can be seen from the figure that the nano-CaCO3 is monodispersed in the vinyl chloride with a size of 5-40nm and no agglomeration.
[0041] Figure 2 The sample strip comparison photos of the ordinary PVC prepared in comparative example 1 of the present invention and the CaCO3 / PVC nanocomposite material prepared in Example 4 are shown. The background is thick black lines hand-drawn on white paper. It can be seen that the transparency of the composite material is good and there is no obvious change compared with the pure polymer material.
[0042] Figure 3 This is a SEM photograph of the tensile fracture surface of the CaCO3 / PVC nanocomposite material prepared in Example 4 of the present invention; as can be seen from the figure, the fracture surface is wavy and interwoven, which explains the inherent structural mechanism of the significant improvement of the elongation at break.
[0043] Figure 4This is a SEM photograph of the impact fracture surface of the CaCO3 / PVC nanocomposite material prepared in Example 4 of the present invention. As can be seen from the figure, the fracture surface is interwoven and extended in a network-like manner, which explains the internal structural mechanism of the greatly improved impact strength. DETAILED DESCRIPTION
[0044] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0045] As one aspect of the present invention, a CaCO3 / PVC nanocomposite material of the present invention comprises the following materials:
[0046] CaCO3 / PVC nanocomposite resin 100 - 120 parts,
[0047] Heat stabilizer 1 - 6 parts,
[0048] Lubricant 0.5 - 2 parts;
[0049] The CaCO3 / PVC nano composite resin is synthesized from the following raw materials in parts by weight: transparent or translucent polyvinyl chloride phase dispersion of nano CaCO3, 4-6 parts of suspension polymerization dispersant, and 0.1-0.3 parts of initiator.
[0050] The transparent or translucent vinyl chloride phase dispersion of nano-CaCO3 comprises 100 parts of vinyl chloride and 8-20 parts of nano-CaCO3.
[0051] The elongation at break of the nanocomposite material is 40%-60%, and the notched impact strength is 4KJ / m 2 -8KJ / m 2 , the tensile yield strength is 55MPa-75MPa. Compared with the PVC material without adding nano-CaCO3, the mechanical properties of the CaCO3 / PVC nano-composite material of the present invention are as follows: the tensile elongation at break is increased by more than 350%, the notched impact strength is increased by more than 200%, and the tensile yield strength is increased by more than 10%; the nano-CaCO3 is monodispersed in the binary composite material with a particle size of 5-40nm.
[0052] In certain embodiments, the heat stabilizer is preferably selected from one of an organic tin stabilizer and a calcium zinc stabilizer.
[0053] In certain preferred embodiments, the lubricant is selected from one of stearic acid lubricant and oxidized polyethylene lubricant.
[0054] In certain embodiments, the suspension polymer dispersant is a mixture of a cellulose dispersant and polyvinyl alcohol, and the weight ratio of the cellulose dispersant to the polyvinyl alcohol is 3:7-7:3; preferably, the cellulose dispersant is selected from one of hydroxypropyl methylcellulose and methylcellulose.
[0055] In certain preferred embodiments, the initiator is selected from a mixture of two or more of ammonium persulfate, potassium persulfate, and an organic peroxide; the organic peroxide is one of tert-butyl peroxydecanoate (Tx23), isophenyl peroxydecanoate (TX99), tert-butyl peroxypivalate (Tx125), tert-butyl peroxyoctanoate (Tx257), and bis-(2-ethylhexyl) peroxydicarbonate (EPH).
[0056] In certain embodiments, the CaCO3 / PVC nanocomposite material further comprises 5-20 parts of an elastomer, thereby forming a CaCO3 / elastomer / PVC ternary nanocomposite material.
[0057] The elongation at break of the above-mentioned ternary nanocomposite material is 100%-260%, and the notched impact strength is 40KJ / m 2 -100KJ / m 2 , the tensile yield strength is 40MPa-60MPa. Compared with ordinary PVC, the elongation at break is increased by more than 400%, the notched impact strength is increased by more than 1000%, and the tensile yield strength is increased by more than 5%; compared with elastomer / PVC composite materials, the elongation at break is increased by more than 300%, the notched impact strength is increased by more than 400%, and the tensile yield strength is increased by more than 15%.
[0058] As another aspect of the present invention, a method for preparing a CaCO3 / PVC nanocomposite material comprises the following steps:
[0059] It is characterized by comprising the following steps:
[0060] 1) Adding nano-CaCO3 and vinyl chloride monomer into a polymerization kettle, stirring is started, and stirring is performed at room temperature for a period of time to form a transparent or translucent nano-CaCO3 vinyl chloride phase dispersion, which can be used as a raw material for synthesizing a nano-composite resin, and the dispersion can exist stably;
[0061] 2) After adding the suspension polymerization aid and water into the polymerization kettle, stirring and heating to the polymerization temperature to start the polymerization reaction;
[0062] 3) After a period of reaction, water is injected midway, and the reaction is continued. When the pressure of the kettle drops below 0.1 MPa, a terminator is added to terminate the reaction, stirring is stopped, and the material is discharged to obtain a suspension of nano-CaCO3 / PVC composite resin;
[0063] 4) The suspension is dehydrated and dried to obtain CaCO3 / PVC nanocomposite resin powder;
[0064] 5) Mechanically blending the CaCO3 / PVC nanocomposite resin powder, a heat stabilizer and a lubricant, and then injection molding or extrusion molding to obtain a CaCO3 / PVC binary nanocomposite material; or mechanically blending the CaCO3 / PVC nanocomposite resin powder, a heat stabilizer, a lubricant and an elastomer, and then injection molding or extrusion molding to obtain a CaCO3 / elastomer / PVC ternary nanocomposite material.
[0065] The method of the present invention stirs the modified nano-CaCO3 solid and vinyl chloride monomer at room temperature to first form a monodisperse, transparent or translucent nano-CaCO3 liquid phase dispersion in vinyl chloride, then adds a suspension polymerization auxiliary agent, and adds water in batches. The specific adding sequence is used to maintain the dispersibility of the nano-CaCO3 until the polymerization reaction is completed, so as to obtain a composite resin of monodisperse nano-CaCO3 in a PVC matrix. The maintained dispersibility of the nano-CaCO3 also brings a more beneficial effect - the good transparency and comprehensive mechanical properties of the finally prepared binary nano-composite material.
[0066] The principle of the present invention is: relying on the good affinity of nano-CaCO3 particles with vinyl chloride monomer and good dispersibility in vinyl chloride, during the polymerization process of vinyl chloride monomer, the monodispersed nano-CaCO3 particles therein are subsequently added to the free base group or original particles or primary particle core or primary particles of PVC, and finally the nano-CaCO3 particles are monodispersed in the PVC resin and have good compatibility; this specific feeding method and sequence maintains the monodispersity of nano-CaCO3 during the polymerization process, and gives full play to the toughening and reinforcing effect of nano-CaCO3 on the finally prepared nano-composite material.
[0067] In the present invention, the elastomer can toughen the rigid PVC and improve its toughness, which has been proven to be an effective method, but at the same time it often leads to a significant reduction in its strength and stiffness while enhancing the toughness. The inorganic nanofiller nano-CaCO3 contributes to the strength and stiffness of the polymer to a certain extent, and synergizes with the elastomer to have a synergistic toughening effect on PVC. Compared with the PVC / elastomer material, the CaCO3 / elastomer / PVC ternary nanocomposite material not only greatly improves the toughness of PVC, but also plays a certain role in protecting and maintaining the strength and stiffness of the material.
[0068] Example 1
[0069] The preparation method of CaCO3 / PVC binary nanocomposite material comprises the following steps:
[0070] Step 1: After adding 30g of nano-CaCO3 and 1000g of vinyl chloride monomer into a polymerization kettle, start stirring at a stirring speed of 1000r / min and stir at room temperature for 25min; add a mixed aqueous solution of 25g of hydroxypropyl methylcellulose ether, 25g of polyvinyl alcohol, 1gEPH, 0.5g of Tx99 and 1g of ammonium bicarbonate, stir for 30min and then heat to 60°C to start polymerization reaction; 30min after the start of the polymerization reaction, inject 2000g of water, react for another 3.5h, add a terminator, end the reaction, and when the kettle pressure drops to 0.1MPa, end stirring and discharge; the obtained CaCO3 / PVC nano-composite resin suspension is dehydrated and dried to obtain CaCO3 / PVC nano-composite resin powder.
[0071] Step 2: Mechanically blend 3 parts of an organic tin stabilizer, 1 part of a stearic acid lubricant and 100 parts of the CaCO3 / PVC nanocomposite resin powder of this embodiment, and perform injection molding.
[0072] A transparent CaCO3 / PVC nanocomposite material was obtained. Compared with comparative example 1, its notched impact strength was increased by 57%, its tensile elongation at break was increased by 127%, and its tensile yield strength was increased by 13%. The mechanical properties thereof are shown in Table 1 below.
[0073] Example 2
[0074] The preparation method of the CaCO3 / PVC nanocomposite material of this embodiment is different from that of Example 1 in that the mass of nano-CaCO3 added in step one is 50 g; a transparent CaCO3 / PVC nanocomposite material is obtained, and compared with comparative example 1, its notched impact strength is increased by 93%, its tensile elongation at break is increased by 192%, and its tensile yield strength is increased by 9.5%; its mechanical properties are shown in Table 1 below.
[0075] Example 3
[0076] The preparation method of the CaCO3 / PVC nanocomposite material of this embodiment is different from that of Example 1 in that the mass of nano-CaCO3 added in step one is 80 g; a transparent CaCO3 / PVC nanocomposite material is obtained, and compared with comparative example 1, its notched impact strength is increased by 110%, its tensile elongation at break is increased by 304%, and its tensile yield strength is increased by 7.2%; its mechanical properties are shown in Table 1 below.
[0077] Example 4
[0078] The preparation method of the CaCO3 / PVC nanocomposite material of this embodiment is different from that of Example 1 in that the mass of nano-CaCO3 added in step one is 100 g; a transparent CaCO3 / PVC nanocomposite material is obtained, and compared with comparative example 1, its notched impact strength is increased by 204%, its tensile elongation at break is increased by 368%, and its tensile yield strength is increased by 4.4%; its mechanical properties are shown in Table 1 below.
[0079] Figure 2 Comparison photos of the strips of ordinary PVC prepared in Comparative Example 1 of the present invention (above) and the CaCO3 / PVC nanocomposite material prepared in this embodiment (below), with the background being thick black lines hand-drawn on white paper. It can be seen that the transparency of the composite material is good, with no obvious change compared with the pure polymer material.
[0080] Figure 3 This is a SEM photograph of the tensile fracture surface of the CaCO3 / PVC nanocomposite material prepared in this embodiment; as can be seen from the figure, the fracture surface is wavy and intertwined, which explains the internal structural mechanism of the significant improvement of the elongation at break.
[0081] Figure 4 This is a SEM photograph of the impact fracture surface of the CaCO3 / PVC nanocomposite material prepared in this embodiment; as can be seen from the figure, the fracture surface is interwoven and extended in a network-like manner, which explains the inherent structural mechanism of the significant improvement in the notched impact strength.
[0082] Example 5
[0083] The preparation method of the CaCO3 / PVC nanocomposite material of this embodiment is different from that of Example 1 in that the mass of nano-CaCO3 added in step one is 120 g; the transparent CaCO3 / PVC nanocomposite material is obtained, and compared with Comparative Example 1, its notched impact strength is increased by 110%, the tensile elongation at break is increased by 312%, and the tensile yield strength is basically the same; its mechanical properties are shown in Table 1 below.
[0084] From Examples 1 to 5, it can be seen that preferably, the added mass of modified CaCO3 is 8-20 parts;
[0085] Example 6
[0086] Preparation of CaCO3 / elastomer / PVC ternary nanocomposite materials:
[0087] The preparation method of the CaCO3 / PVC nanocomposite material in this embodiment is different from that in Example 1 in that the mass of the nano-CaCO3 added in step 1 is 100 g;
[0088] 3 parts of an organic tin stabilizer, 1 part of a stearic acid lubricant, 100 parts of the CaCO3 / PVC nanocomposite resin powder of this embodiment and 10 parts of MBS were mixed and injection molded.
[0089] The obtained CaCO3 / PVC / MBS ternary nanocomposite material has a notched impact strength increased by 180%, a tensile elongation at break increased by 270%, and a tensile yield strength increased by 13% compared with comparative example 2; its mechanical properties are shown in Table 1 below.
[0090] Example 7
[0091] The preparation method of the CaCO3 / PVC nanocomposite material in this embodiment is different from that in Example 1 in that the mass of the nano-CaCO3 added in step 1 is 100 g;
[0092] 3 parts of organotin stabilizer, 1 part of stearic acid lubricant, 100 parts of CaCO3 / PVC nanocomposite resin powder of this embodiment and 10 parts of CPE were mechanically blended and injection molded.
[0093] The obtained CaCO3 / PVC / CPE ternary nanocomposite material has a notched impact strength increased by 348.8%, a tensile elongation at break increased by 158.3%, and a tensile yield strength increased by 2.5% compared with comparative example 3; its mechanical properties are shown in Table 1 below.
[0094] Example 8
[0095] The preparation method of the CaCO3 / PVC nanocomposite material in this embodiment is different from that in Example 1 in that the mass of the nano-CaCO3 added in step 1 is 100 g;
[0096] 3 parts of organotin stabilizer, 1 part of stearic acid lubricant, 100 parts of CaCO3 / PVC nanocomposite resin powder of this embodiment and 10 parts of ACR were mixed and injection molded.
[0097] The obtained CaCO3 / PVC / ACR ternary nanocomposite material has a notched impact strength increased by 150%, a tensile elongation at break increased by 110%, and a tensile yield strength increased by 5% compared with comparative example 4; its mechanical properties are shown in Table 1 below.
[0098] Comparative Example 1
[0099] The preparation method of ordinary PVC material includes the following steps:
[0100] Step 1: After adding 1000g of vinyl chloride monomer into a polymerization kettle, start stirring, stir at a stirring speed of 1000r / min, and stir at room temperature for 25min; add a mixed aqueous solution of 25g of hydroxypropyl methylcellulose ether, 25g of polyvinyl alcohol, 1g of EPH, 0.5g of Tx99 and 1g of ammonium bicarbonate, stir for 30min and then heat to 60°C to start polymerization reaction; 30min after the polymerization reaction starts, inject 2000g of water, react for another 3.5h, add a terminator, end the reaction, and when the kettle pressure drops to 0.1MPa, end stirring and discharge; the obtained PVC resin suspension is dehydrated and dried to obtain PVC resin powder.
[0101] Step 2: Mechanically blend 3 parts of an organic tin stabilizer, 1 part of a stearic acid lubricant and 100 parts of the PVC resin powder of this embodiment, and perform injection molding to obtain a common PVC material; the mechanical properties of the material are shown in Table 2 below.
[0102] Comparative Example 2
[0103] A method for preparing a PVC / MBS binary composite material comprises the following steps:
[0104] Step 1: After adding 1000g of vinyl chloride monomer into the polymerization kettle, start stirring, stir at a stirring speed of 1000r / min, and stir at room temperature for 25min; add a mixed aqueous solution of 25g of hydroxypropyl methylcellulose ether, 25g of polyvinyl alcohol, 1g of EPH, 0.5g of Tx99 and 1g of ammonium bicarbonate, stir for 30min and then heat to 60°C to start the polymerization reaction; 30min after the start of the polymerization reaction, inject 2000g of water, react for another 3.5h, add a terminator, end the reaction, and when the kettle pressure drops to 0.1MPa, end stirring and discharge; obtain a suspension of PVC composite resin, and the suspension is dehydrated and dried to obtain PVC resin powder.
[0105] Step 2: Mechanically blend 3 parts of an organic tin stabilizer, 1 part of a stearic acid lubricant, 100 parts of the PVC resin powder of this embodiment and 10 parts of MBS, and perform injection molding to obtain a PVC / MBS binary composite material; the mechanical properties of the composite material are shown in Table 2 below.
[0106] Comparative Example 3
[0107] A method for preparing a PVC / CPE binary composite material comprises the following steps:
[0108] Step 1: After adding 1000g of vinyl chloride monomer into a polymerization kettle, start stirring, stir at a stirring speed of 1000r / min, and stir at room temperature for 25min; add a mixed aqueous solution of 25g of hydroxypropyl methylcellulose ether, 25g of polyvinyl alcohol, 1g of EPH, 0.5g of Tx99 and 1g of ammonium bicarbonate, stir for 30min and then heat to 60°C to start polymerization reaction; 30min after the start of the polymerization reaction, inject 2000g of water, react for another 3.5h, add a terminator, end the reaction, and when the kettle pressure drops to 0.1MPa, end stirring and discharge; the obtained PVC resin suspension is dehydrated and dried to obtain PVC resin powder.
[0109] Step 2: Mechanically blend 3 parts of an organic tin stabilizer, 1 part of a stearic acid lubricant, 100 parts of the PVC resin powder of this embodiment and 10 parts of CPE, and perform injection molding to obtain a PVC / CPE binary composite material; the mechanical properties of the composite material are shown in Table 2 below.
[0110] Comparative Example 4
[0111] A method for preparing a PVC / ACR binary composite material comprises the following steps:
[0112] Step 1: After adding 1000g of vinyl chloride monomer into a polymerization kettle, start stirring, stir at a stirring speed of 1000r / min, and stir at room temperature for 25min; add a mixed aqueous solution of 25g of hydroxypropyl methylcellulose ether, 25g of polyvinyl alcohol, 1g of EPH, 0.5g of Tx99 and 1g of ammonium bicarbonate, stir for 30min and then heat to 60°C to start polymerization reaction; 30min after the start of the polymerization reaction, inject 2000g of water, react for another 3.5h, add a terminator, end the reaction, and when the kettle pressure drops to 0.1MPa, end stirring and discharge; the obtained PVC resin suspension is dehydrated and dried to obtain PVC resin powder.
[0113] Step 2: Mechanically blend 3 parts of an organic tin stabilizer, 1 part of a stearic acid lubricant, 100 parts of the PVC resin powder of this embodiment and 10 parts of ACR, and perform injection molding to obtain a PVC / ACR binary composite material; the mechanical properties of the composite material are shown in Table 2 below.
[0114] Comparative Example 5
[0115] A method for preparing a CaCO3 / PVC nanocomposite material comprises the following steps:
[0116] Step 1: After adding 100g of ordinary nano-CaCO3 and 1000g of vinyl chloride monomer into a polymerization kettle, start stirring, stir at a stirring speed of 1000r / min, and stir at room temperature for 25min; add a mixed aqueous solution of 25g of hydroxypropyl methylcellulose ether, 25g of polyvinyl alcohol, 1g of EPH, 0.5g of Tx99 and 1g of ammonium bicarbonate, stir for 30min and then heat to 60°C to start polymerization reaction; 30min after the start of the polymerization reaction, inject 2000g of water, react for another 3.5h, add a terminator, end the reaction, and when the kettle pressure drops to 0.1MPa, end stirring and discharge; obtain a suspension of commercially available CaCO3 / PVC nano-composite resin, and the suspension is dehydrated and dried to obtain a commercially available CaCO3 / PVC nano-composite resin powder.
[0117] Step 2: Mechanically blend 3 parts of an organic tin stabilizer, 1 part of a stearic acid lubricant and 100 parts of the CaCO3 / PVC nanocomposite resin powder of this embodiment, and perform injection molding to obtain a CaCO3 / PVC nanocomposite material; the mechanical properties of the material are shown in Table 2 below.
[0118] Comparative Example 6
[0119] A method for preparing a CaCO3 / PVC / MBS ternary nanocomposite material comprises the following steps:
[0120] Step 1: After adding 100g of ordinary nano-CaCO3 and 1000g of vinyl chloride monomer into a polymerization kettle, start stirring, stir at a stirring speed of 1000r / min, and stir at room temperature for 25min; add a mixed aqueous solution of 25g of hydroxypropyl methylcellulose ether, 25g of polyvinyl alcohol, 1g of EPH, 0.5g of Tx99 and 1g of ammonium bicarbonate, stir for 30min and then heat to 60°C to start polymerization reaction; 30min after the start of the polymerization reaction, inject 2000g of water, react for another 3.5h, add a terminator, end the reaction, and when the kettle pressure drops to 0.1MPa, end stirring and discharge; the obtained commercially available CaCO3 / PVC nano-composite resin suspension is dehydrated and dried to obtain a commercially available CaCO3 / PVC nano-composite resin powder.
[0121] Step 2: Mechanically blend 3 parts of organic tin stabilizer, 1 part of stearic acid lubricant, 100 parts of CaCO3 / PVC nanocomposite resin powder of this embodiment and 10 parts of MBS, and injection mold them; obtain a CaCO3 / PVC / MBS ternary nanocomposite material; its mechanical properties are shown in Table 2 below.
[0122] Comparative Example 7
[0123] The method for preparing an opaque CaCO3 / PVC nanocomposite material comprises the following steps:
[0124] Step 1: After adding 1000g of vinyl chloride monomer into a polymerization kettle, start stirring, stir at a stirring speed of 1000r / min, and stir at room temperature for 25min; add a mixed aqueous solution of 25g of hydroxypropyl methylcellulose ether, 25g of polyvinyl alcohol, 1g of EPH, 0.5g of Tx99 and 1g of ammonium bicarbonate, stir for 30min and then heat to 60°C to start polymerization reaction; 30min after the start of the polymerization reaction, inject 2000g of water, react for another 3.5h, add a terminator, end the reaction, and when the kettle pressure drops to 0.1MPa, end stirring and discharge; the obtained PVC resin suspension is dehydrated and dried to obtain PVC resin powder.
[0125] Step 2: Mechanically blend 3 parts of an organic tin stabilizer, 1 part of a stearic acid lubricant, 10 parts of the nano-CaCO3 used in the present invention, and 100 parts of the PVC resin powder of this embodiment, and perform injection molding to obtain an opaque CaCO3 / PVC nano-composite material; the mechanical properties of the composite material are shown in Table 2 below.
[0126] Table 1: Mechanical properties of the composite materials obtained in each example
[0127]
[0128] Table 2 Mechanical properties of materials obtained in comparative examples
[0129]
[0130] From the data in Table 1 and Table 2 above, we can see that:
[0131] 1) The CaCO3 / PVC binary nanocomposite material prepared by the present invention and the derived CaCO3 / elastomer / PVC ternary nanocomposite material have greatly improved elongation at break and impact strength compared with ordinary PVC. While toughening, the strength of the composite material is also improved.
[0132] 2) The present invention is simple to operate, greatly improves the overall mechanical properties of the CaCO3 / PVC binary nanocomposite material and its derived CaCO3 / elastomer / PVC ternary nanocomposite material, especially the elongation at break is significantly improved, and the production cost of PVC materials is reduced. Without adding other additives, the binary composite material itself also has good transparency.
[0133] 3) On the basis of the original application fields, the application of CaCO3 / PVC binary composite materials with high mechanical properties can be further expanded in the field of hard transparent plastic products, such as plastic glass, transparent plates, etc., reducing the use of impact-resistant additives in the preparation process and improving economic benefits. Therefore, it has a very broad prospect in production application.
[0134] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A CaCO3 / PVC nanocomposite material, characterized in that: Including the following materials: CaCO3 / PVC nanocomposite resin 100 - 120 parts, Heat stabilizer 1 - 6 parts, Lubricant 0.5 - 2 parts; The CaCO3 / PVC nanocomposite resin is synthesized from the following raw materials in parts by weight: a transparent or translucent vinyl chloride phase dispersion of nano-CaCO3, 4-6 parts of a suspension polymerization dispersant, and 0.1-0.3 parts of an initiator; The transparent or translucent vinyl chloride phase dispersion of nano-CaCO3 comprises 100 parts of vinyl chloride and 8-20 parts of nano-CaCO3.
2. The CaCO3 / PVC nanocomposite material according to claim 1, characterized in that: The heat stabilizer is a commonly used stabilizer in industrial production, selected from one of an organic tin stabilizer and a calcium zinc stabilizer; The lubricant is selected from one of stearic acid lubricant and oxidized polyethylene lubricant.
3. The CaCO3 / PVC nanocomposite material according to claim 1, characterized in that: The CaCO3 / PVC nanocomposite material also includes 5-20 parts of an elastomer, thereby forming a CaCO3 / elastomer / PVC ternary nanocomposite material.
4. A method for preparing a CaCO3 / PVC nanocomposite material as claimed in any one of claims 1 to 3, characterized in that: The steps include: 1) Adding nano-CaCO3 and vinyl chloride monomer into a polymerization kettle, stirring is started, and stirring is performed at room temperature for a period of time to form a transparent or translucent nano-CaCO3 vinyl chloride phase dispersion, which can be used as a raw material for synthesizing a nano-composite resin, and the dispersion can exist stably; 2) After adding the suspension polymerization aid and water into the polymerization kettle, stirring and heating to the polymerization temperature to start the polymerization reaction; 3) After a period of reaction, water is injected midway, and the reaction is continued. When the pressure of the kettle drops below 0.1 MPa, a terminator is added to terminate the reaction, stirring is stopped, and the material is discharged to obtain a suspension of nano-CaCO3 / PVC composite resin; 4) The suspension is dehydrated and dried to obtain CaCO3 / PVC nanocomposite resin powder; 5) Mechanically blending CaCO3 / PVC nanocomposite resin powder, a heat stabilizer and a lubricant, and then injection molding or extrusion molding to obtain a CaCO3 / PVC nanocomposite material; or mechanically blending CaCO3 / PVC nanocomposite resin powder, a heat stabilizer, a lubricant and an elastomer, and then injection molding or extrusion molding to obtain a CaCO3 / elastomer / PVC ternary nanocomposite material.
5. The preparation method according to claim 4, characterized in that: In step 1), the added amounts of nano-CaCO3 and vinyl chloride monomer are 8-20 parts and 100 parts respectively, and the stirring speed and stirring time are 500r / min-1500r / min and 15min-30min respectively.
6. The preparation method according to claim 4, characterized in that: The suspension polymerization aid in step 2) is composed of 4-6 parts of suspension polymerization dispersant, 0.1-0.3 parts of initiator, and 0.05-0.15 parts of pH regulator. The amount of water added is 50-150 parts, the stirring time is 20min-30min, and the polymerization temperature is 50°C-65°C. Wherein, the suspension polymerization dispersant is a mixture of a cellulose dispersant and polyvinyl alcohol, and the weight ratio of the cellulose dispersant to the polyvinyl alcohol is 3:7-7:3; preferably, the cellulose dispersant is selected from one of hydroxypropyl methylcellulose and methylcellulose; The initiator is selected from a mixture of two or more of ammonium persulfate, potassium persulfate, and an organic peroxide; preferably, the organic peroxide is one of tert-butyl peroxydecanoate, isophenyl peroxydecanoate, tert-butyl peroxypivalate, tert-butyl peroxyoctanoate, and bis-(2-ethylhexyl) peroxydicarbonate; The pH regulator is selected from one of ammonium bicarbonate, ammonia water and sodium bicarbonate.
7. The preparation method according to claim 4, characterized in that: In step 3), the reaction period refers to 20-40 minutes of reaction, the amount of water added in the mid-injection is 150-250 parts, and the reaction time is 3-4 hours.
8. The preparation method according to claim 4, characterized in that: In step 5), the amount of the heat stabilizer added is 1-6 parts, the amount of the lubricant added is 0.5-2 parts, and the amount of the elastomer added is 5-20 parts.
9. The preparation method according to claim 8, characterized in that: The heat stabilizer is selected from one of an organic tin stabilizer and a calcium zinc stabilizer; The lubricant is selected from one of stearic acid lubricant and oxidized polyethylene lubricant.
Citation Information
Patent Citations
Method for polymerizing polyvinyl chloride (PVC) resin by virtue of in-situ suspension
CN102199233A
Suspension polymerization method of polyvinyl chloride / nanometer calcium carbonate composite resin
CN108586969A
Method for improving production efficiency of polyvinyl chloride composite resin
CN113980161A
Transparent liquid-phase dispersion formed by nano calcium carbonate monodispersed in organic reagent and preparation method of transparent liquid-phase dispersion
CN116082859A
Polyvinyl chloride low-temperature toughening modifier and polyvinyl chloride composition containing low-temperature toughening modifier
WO2017182003A1